Intersections between design, health and sustainability: the case of wearables - Canetti, Rocío Belén (2023)
Within the framework of the GIDSu project, we wonder where sustainable design will mutate considering the paths in socio-technical and transition innovation. In the area of Health and Medicine we locate the field of wearables; an emerging scenario that uses complex productsservices- systems interconnected to various actors through IoT. This expanding market presents some barriers that complicate its adoption. Among them the concern regarding how to project wearables in terms of sustainable development and how to design the experience to ensure their widespread use. The objective of this work is to survey the cases of wearables that exist today in the field of health at a global level and characterize this sample. For that, concepts of Design for transition and Experience Design are taken up. Two sets of cases of interest were identified: wearables with user-centered design, associated with sport and well-being; and another of wearables with an expanded or human-centered design, with an expanded vision of the health service and some first approaches tending to a human-centered design.